Positive Distraction and Passive Dispersion in the Interior Space of Office Buildings - Al Dabbagh, Shamael Mohamed; Al Khazaali, Lina Kifah Kadhum (Iraqi Journal of Architecture and Planning, 2017)
The office building linked to the performance of visual tasks of work environments and reflect the progress of society and the one most in need to take into account the psychological dimension (dispersion and distraction) When designed especially as an area of practice where multiple activities, carried out by the staff (users boarders) with a temperament and different personalities, and frequented by users external diverse, all of this requires taking into account the different segments during the design process to integrate the system and have the final product work efficient motivates employees and increases their activity , So the research problem has been identified by (the lack of a clear vision for the role of " Positive Distraction and Passive Dispersion ," in relation with the settings (spatial elements of architectural design , detailes of interior space) , and its impact on the employee’s performance today. The research aims to find a clear vision on the impact of spatial settings and detailed design elements carrying out for positive distraction and passive dispersion within the atmosphere of the internal environment of the office spaces, which will achieve convenience, job satisfaction and reflected positively on employee’s performance at work environment in the end.